1976
DOI: 10.1073/pnas.73.9.2955
|View full text |Cite
|
Sign up to set email alerts
|

An equation of state describing hydrophobic interactions

Abstract: Several thermodynamic properties for the process of dissolution of pure hydrocarbons into water are found to be linearly related to the number of hydrogens on the hydrocarbon molecule. From the correlations found for the Gibbs energy change, enthalpy change, and heat capacity change, along with the use of an average minimum solubility temperature, an equation of state for the hydrophobic effect is derived. The entropy change upon dissolution per hydrocarbon hydrogen atom is close to -R In 2. A model based upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
101
0
5

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(117 citation statements)
references
References 3 publications
11
101
0
5
Order By: Relevance
“…The negative contribution (-7.0 J K" mol") for the apolar hydrogen is similar to that published previously (Gill & Wadso, 1976). The negative contribution of the hydroxyl, on the other hand, is considerably less in magnitude than that reported by Privalov and Makhatadze (1990) based on gas dissolution studies.…”
Section: Contributions To As'supporting
confidence: 89%
See 1 more Smart Citation
“…The negative contribution (-7.0 J K" mol") for the apolar hydrogen is similar to that published previously (Gill & Wadso, 1976). The negative contribution of the hydroxyl, on the other hand, is considerably less in magnitude than that reported by Privalov and Makhatadze (1990) based on gas dissolution studies.…”
Section: Contributions To As'supporting
confidence: 89%
“…Additionally, the results of such studies provide important information on the interaction between solute functional groups and water through the changes in entropy and heat capacity. Such information has been invaluable in understanding the hydrophobic effect (Gill & Wadso, 1976;Baldwin, 1986; and in modeling the temperature dependence of biological processes in solution (Privalov & Makhatadze, 1992;Gomez et al, 1995).…”
mentioning
confidence: 99%
“…(3)- (6) obviously rests on the assumption of additivity of the contributions of individual chemical groups to the total solvation entropy and enthalpy, an assumption which has been independently verified. 13,47,48 The other, more serious, assumption is that it is sufficient to sort the solvation contributions of all chemical groups into just two groups, hydrophilic and hydrophobic, characterized by the variable X , an assumption which we show not to be entirely true in this paper. In fact, the concept of entropy convergence treated theoretically by the information theory approach and revised scaled particle theory in some sense goes beyond the additivity concept outlined above, 19,22,23 since here it is shown that the entropy of solvation of hard spheres converges to a universal value at one temperature for a whole range of different sphere radii.…”
Section: S(t ) = S(tmentioning
confidence: 91%
“…由于表面活性剂的亲水部分在 胶束形成前后始终与水接触, 而疏水部分在胶束形成前 暴露于水相, 在胶束形成后才会迁移到聚集体的非极性 内核中, 因此, 表面活性剂分子的疏水部分所处环境的 变化更大. ΔC p,mic 的数值正是反映表面活性剂在胶束化 前后所处环境变化的热力学参数, 该数值的大小能够近 似地反映表面活性剂分子中暴露于水相的疏水部分面 积在胶束化过程中的变化情况 [12,13] . 因此, 通过 ΔC p,mic 的数值可以推测表面活性剂的聚集体结构.…”
unclassified